Accumulation of dietary methylmercury and effects on growth and survival in two estuarine forage fish: Cyprinodon variegatus and Menidia beryllina. (26th February 2013) - Stefansson, Emily S.; Heyes, Andrew; Rowe, Christopher L.
Abstract Dietary methylmercury (MeHg) uptake by fish in relation to life stage, species, and level of exposure is poorly understood in lower trophic levels, particularly in estuarine species. The authors compared accumulation of dietary MeHg as well as sensitivity (survival and growth) to dietary MeHg exposure in two species of estuarine forage fish, Cyprinodon variegatus and Menidia beryllina. Fish were fed one of five dietary MeHg concentrations (ranging from 0.04 to 14 µg/g dry wt) over a period of 70 d. Growth rate and the level of dietary exposure influenced MeHg tissue concentrations in both species. Mercury in the diet exhibited a strong linear relationship with fish Hg tissue concentrations. Additionally, the authors found that M. beryllina was more sensitive to dietary MeHg exposure than C. variegatus. Both species showed some decreases in growth related to MeHg exposure, although these patterns were not consistent among treatments. Overall, C. variegatus and M. beryllina were found to have a high tolerance for dietary MeHg exposure. If fish occupying low trophic levels are capable of surviving with high Hg body burdens, this tolerance has important implications for Hg exposure of organisms occupying higher trophic levels. Environ. Toxicol. Chem. 2013;32:848–856. © 2013 SETAC